2019
DOI: 10.1039/c8nr09446b
|View full text |Cite
|
Sign up to set email alerts
|

Solvent exfoliation stabilizes TiS2 nanosheets against oxidation, facilitating lithium storage applications

Abstract: Titanium disulfide is a promising material for a range of applications, including lithium-ion battery (LIB) anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 67 publications
1
56
0
Order By: Relevance
“…After a number of annealing steps, we obtained a black polycrystalline substance which powder X-ray diffraction (XRD) analysis ( Figure 1A, and Figure S1 and Table S1, Supporting Information) showed to be 97% SnP 3 with 3% Sn 3 P 4 as a minority phase. Such bulk samples can be converted into nanosheets (see Figure 1b for structure) using liquid phase exfoliation [9,30,[34][35][36] by sonicating the powder in N-methyl-pyrrolidone (NMP) before removing unexfoliated material by centrifugation. The resulting sample was a black liquid with a solid content of 1-3 g L −1 ( Figure 1B).…”
Section: Liquid Exfoliation Of Snpmentioning
confidence: 99%
See 1 more Smart Citation
“…After a number of annealing steps, we obtained a black polycrystalline substance which powder X-ray diffraction (XRD) analysis ( Figure 1A, and Figure S1 and Table S1, Supporting Information) showed to be 97% SnP 3 with 3% Sn 3 P 4 as a minority phase. Such bulk samples can be converted into nanosheets (see Figure 1b for structure) using liquid phase exfoliation [9,30,[34][35][36] by sonicating the powder in N-methyl-pyrrolidone (NMP) before removing unexfoliated material by centrifugation. The resulting sample was a black liquid with a solid content of 1-3 g L −1 ( Figure 1B).…”
Section: Liquid Exfoliation Of Snpmentioning
confidence: 99%
“…A number of studies have shown that liquid‐processed, exfoliated nanosheets yield electrodes with much better capacity and stability than those fabricated from unexfoliated layered particles. [ 27 ] In addition, it has been shown that replacing the conductive additive and binder with a network of carbon nanotubes can maximize charge storage capacity for electrodes fabricated from both 2D [ 28–30 ] and non‐2D [ 18 ] based electrodes. In addition, the presence of nanotubes toughens the electrode dramatically, increasing the achievable film thickness, and significantly increases the conductivity, [ 31 ] laying the foundations for good rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, potential degradation due to chemical reactions with water and air can be supressed as demonstrated for black phosphorous 24 and TiS2. 40 Dispersions obtained by LPE are intrinsically polydisperse, containing nanosheets with broad size and thickness distributions. To gain insights into size-dependent properties, a method for size selection is required.…”
Section: Exfoliation and Size Selectionmentioning
confidence: 99%
“…Prior to the measurement, samples were refreshed by bath sonication to avoid potential impact from sedimentation similar to previous work. 23,24,40,57 Extinction spectra from the small-sized sheets (3-10k g) stored at 20°C and 40°C for up to 488 hours are shown in figure 5A and 5B, respectively. Extinction and absorbance spectra of other sizes and storage conditions are shown in the SI (Figure S10, S12).…”
Section: Stability Of Ni2p2s6 Nanosheetsmentioning
confidence: 99%
“…[21][22][23] This method yields dispersions with nanosheet concentrations of ~gL -nanosheets with broad size distributions, 18,27 ensembles with large monolayer fractions can be also produced after size selection. 17,18 Due to its simplicity and scalability, 22,28 LPE has been applied to a range of 2D materials including graphene, [29][30][31] BN, 32,33 TMDs, 21,[34][35][36] GaS, 37 InSe, 38 SnS 39 or GeTe 40 among others.…”
Section: Introductionmentioning
confidence: 99%